Differential diagnosis of hypertrophic pachymeningitis: literature review - Makarevičius, G.; Grigaitė, J.; Jokubaitis, M.; Klimašauskienė, A. (Neurologijos seminarai, 2022)
Hypertrophic pachymeningitis (HP) is a focal or diffuse thickening of cranial and/or spinal dura mater caused by chronic inflammatory process, which induces fibrosis and thickening of the pachymeninges. Fibrotic, thickened dura causes compression of adjacent structures that results in HP symptoms. Usually HP presents with headache, diplopia, visual loss, and otologic symptoms. As the disease progresses, intracranial hypertension, consciousness disturbance, and seizures may also develop. There are two distinct groups of HP – idiopathic and secondary HP. There are 3 major groups of secondary HP: infectious, autoimmune, and oncological. There are no highly specific clinical and radiological features to distinguish secondary HP from idiopathic HP. For this reason, a thorough examination and dural biopsy are of great importance in the diagnosis of idiopathic HP. Idiopathic HP can be only diagnosed when secondary causes of HP are ruled out and dural biopsy confirms that there are only unspecific findings: lymphocytic-plasmacytic infiltration and fibrosis. In this article, we review the literature regarding HP and discuss clinical and radiological features of both, idiopathic and secondary HP, and their differential diagnosis.
Keywords: idiopathic hypertrophic pachymeningitis; secondary hypertrophic pachymeningitis; differential diagnosis